INFLUENCE OF ICING ON AIRCRAFT PERFORMANCE OF UNMANNED AERIAL VEHICLE М-10-2 "ОКО" - Matiychyk Мykhailo; Suvorova, Natalya; Tereshchenko, Dmytro; Plakhotniuk, Ievgen; Trachuk, Kateryna (Proceedings of National Aviation University (archive), 2017)
Purpose: Carry out the analysis of lifting surface area of unmanned aerial aircraft. Icing appeared during test flights of unmanned aerial aircraft. Methods: Analysis of flight results in icing conditions using design flight characteristics of unmanned aerial vehicle and data from flight recorder was conducted. The largest ice formations observed on along whole length leading edge of the wing and whole length leading edge of winglets. Results: Under certain meteorological conditions ice deposits forms on parts of small unmanned aerial vehicle similar to how it is formed on a large-sized aircraft was found in practice. Ice formation distorted wing leading edge and front part and bottom and top wing curves. Analogically way tail unit was distorted by ice formations. In addition icing of front surface of telemetry and video antennas, and front part of airspeed sensor tube was found. Formation belongs to pike-shaped type was specified. Discussion: Icing of lifting surface area of aircraft during flight can cause undesirable consequences both in manned and unmanned aviation. Real test flights of unmanned aerial vehicles of SPCUA “Virazh” of National Aviation University in the winter period showed, that ignorance of icing problem could decrease flight safety level up to aviation accident. Fact of icing was discovered after unmanned aerial vehicle landing.